Deciphering Fc-mediated Antiviral Antibody Functions in Animal Models - Schmaljohn, Alan L.; Orlandi, Chiara; Lewis, George K. (Frontiers in Immunology, 2019)
Longstanding discordances and enigmas persist as to the specificities and other properties of antibodies most effective in preventing or limiting many viral infections in mammals; in turn, failure to decipher key complexities has added to headwinds for both antibody-based therapeutic approaches and rational vaccine design. More recently, experimental approaches have emerged—and continue to emerge—for discerning the functional role of antibody structure, especially the Fc portion of antibody, in combating viral infections in vivo. A wide range of in vitro measures of antibody activity, from neutralization to antibody-dependent cell mediated cytotoxicity (ADCC)—each of these terms representing only an operational notion defined by the particulars of a given assay—are poised for assignment of both relevance and reliability in forecasting outcomes of infection. Of the several emergent technical opportunities for clarity, attention here is drawn to three realms: the increasing array of known modifications that can be engineered into antibodies to affect their in vivo activities; the improvement of murine models involving knockouts and knock-ins of host genes including Fc receptors; and the development of additional virological design tools to differentiate antibodies that act primarily by inhibiting viral entry from antibodies that mainly target viral antigens on cell surfaces. To illustrate some of the opportunities with either zoonotic (emerging, spillover) or ancient human-adapted viruses, we draw examples from a wide range of viruses that affect humans.